Calf management - Jones, Jesse McCullah (My University, 1903)
Introduction: WHAT IS A CALF: It is well in the first place to consider the question, What is a calf? and at what age it ceases to be such. In this treatis the age will be limited to twelve months because of its general usage in this way both by the general public and public fair authorities. A few contend that this age is too great, in view of the fact that the calf loses its baby form at eight months of age, but twelve months is the most universal division of ages and is likely to remain so for a long time. The first twelve months of a calf's life determines largely its future usefulness and value, and no greater problem confronts the stockman than that of the rearing of calves and how to secure the best results with them. Improper care and unsufficient nutrition are detrimental to old animals but doubly so to calves. If there is any stinting of feed to be done, let it be with those over twelve months of age. Under twelve months is the best for cheap and effective development and no later care, no matter how scientific or practical, can completely replace that quality lacking because of improper early management. If a calf is not given proper attention, its time and development is extended, if ever it reaches the maximum development it should, again a good healthy condition in calf-hood helps to ward off the diseases calf flesh is heir too. Not only does this matter of early development effect the animal itself, but if a breeding animal, its progeny as well, causing them to give less returns for food consumed, whether for beef or dairy. Many a promising calf at birth is e'er long reduced to the class of common stock by injudicious treatment.
Citation: Jones, Jesse McCullah. Calf management. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Calf; Animal Husbandry; Growth; Nutrition; Theses